Effects of an Intervention to Improve Life-Space Mobility and Self-Efficacy in Patients following Total Knee Arthroplasty - Hiyama, Yoshinori; Kamitani, Tsukasa; Mori, Kazuaki (The Journal of Knee Surgery, 2019)
Life-space mobility describes the spatial areas through which an individual moves, and the frequency and need for assistance. Although patients with knee osteoarthritis (OA) have shown restricted life-space mobility, total knee arthroplasty (TKA) does not improve it beyond preoperative levels. Life-space mobility after TKA was influenced by self-efficacy for walking tasks; thus, an intervention to improve self-efficacy for walking tasks may contribute to better life-space mobility. We provided a walking event including several walking tasks as the intervention. We assessed the effect of the walking event on life-space mobility and self-efficacy for walking tasks in patients following TKA. In this nonrandomized controlled trial, patients who underwent primary TKA were recruited. After recruitment, patients who could not participate in the walking event due to scheduling conflicts were included in the control group. The walking event consisted of 3.5 km of walking course and included walking tasks as follows: crossing at the crosswalk, walking up- and downstairs without a railing, walking along dirt roads, and walking up and down a slope. The primary outcome was life-space mobility measured using Life-Space Assessment (LSA) and self-efficacy for walking tasks measured using the modified Gait Efficacy Scale (mGES). We enrolled 104 patients, of whom 36 were assigned to the intervention group and participated in the walking event. Participants in the intervention group had significantly better LSA score (adjusted mean difference between groups: 13.9; 95% confidence interval: 12.4–15.5; p < 0.001) and mGES score (adjusted mean difference between groups: 13.8; 95% confidence interval: 12.4–15.1; p < 0.001) than the control group even after adjusting for age, gender, body mass index, elapsed time from surgery, the severity of knee OA of nonoperated limb, and patient-reported functional outcome. The walking event including various walking tasks improved life-space mobility and self-efficacy in patients following TKA. It is important to design a program that can improve self-efficacy for walking tasks through mastery experiences to improve life-space mobility after TKA.
Keywords: mobility; activity; self-efficacy; walking task; total knee arthroplasty